ANALISIS KEAKTIFAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA DI SDN CINTAJAYA - Amalia, Nita Aura; Maftuh, Ade; Sidik, Geri Syahril (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
Student learning activity is one of the important indicators in assessing the effectiveness of the learning process, especially in subjects that require understanding of concepts such as mathematics. This study aims to analyze the level of learning activity of grade V students in Mathematics subjects at SDN Cintajaya and identify the factors that influence it. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that student learning activeness was in the moderately active category, but varied between individuals. Some students showed full involvement in learning activities, such as paying attention to the teacher's explanation, asking questions, discussing, and solving problems. Moderately active students tend to depend on teacher direction and are not yet fully independent, while less active students appear passive and face barriers in understanding and motivation. Factors that influence learning activeness include internal factors (motivation, interest, confidence, and understanding of the material), external factors (family support, the role of the teacher, and the classroom atmosphere), and the learning approach used. In conclusion, student learning activeness is the result of interactions between various interrelated factors, so it requires an active role of the teacher and the support of a conducive learning environment to increase student participation optimally. ABSTRAKKeaktifan belajar siswa meupakan salah satu indikator penting dalam menilai efektivitas proses pembelajaran, khususnya pada mata pelajaran yang menuntut pemahaman konsep seperti Matematika. Penelitian ini bertujuan untuk menganalisis tingkat keaktifan belajar siswa kelas V pada mata pelajaran Matematika di SDN Cintajaya serta mengidentifikasi faktor-faktor yang memengaruhinya. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, angket, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa keaktifan belajar siswa berada pada kategori cukup aktif, namun bervariasi antar individu. Beberapa siswa menunjukkan keterlibatan penuh dalam aktivitas pembelajaran, seperti memperhatikan penjelasan guru, bertanya, berdiskusi, serta memecahkan soal. Siswa yang cukup aktif cenderung bergantung pada arahan guru dan belum sepenuhnya mandiri, sementara siswa yang kurang aktif tampak pasif dan menghadapi hambatan dalam pemahaman dan motivasi. Faktor-faktor yang memengaruhi keaktifan belajar meliputi faktor internal (motivasi, minat, kepercayaan diri, dan pemahaman materi), faktor eksternal (dukungan keluarga, peran guru, dan suasana kelas), serta pendekatan pembelajaran yang digunakan. Kesimpulannya, keaktifan belajar siswa merupakan hasil interaksi antara berbagai faktor yang saling berkaitan, sehingga diperlukan peran aktif guru dan dukungan lingkungan belajar yang kondusif untuk meningkatkan partisipasi siswa secara optimal.